Percutaneous needle decompression for tension pneumoperitoneum during GI endoscopy: a step-by-step guide - Natalie J. Wilson, MD; Rahul Karna, MD; Giovanni A. Roldan, MD; Roberto Osorio Cintron, RN; Alexander Leaf, RN; Daniela Guerrero Vinsard, MD; Mohammad Bilal, MD (VideoGIE)
Background and Aims: GI tract perforations during endoscopy can lead to serious adverse events such as tension pneumoperitoneum. In such cases, intraprocedural percutaneous needle decompression can be a lifesaving technique, in addition to allowing procedure completion. The aim of this study is to review the indications for percutaneous needle decompression and provide a step-by-step procedural guide with case examples. Methods: This review article and accompanying video review the technique for percutaneous needle decompression for pneumoperitoneum during endoscopy-related perforation, providing a step-by-step procedural guide illustrated with 2 case examples. Results: In both case examples, intraprocedural needle decompression resulted in rapid normalization of hemodynamics and allowed time to safely complete the procedures after endoscopic closure of the perforation. Conclusions: Early recognition of pneumoperitoneum followed by intraprocedural percutaneous needle decompression with a large-bore catheter can allow time for defect closure and procedure completion or can serve as a temporizing measure until surgical intervention. Endoscopists should be comfortable performing this lifesaving technique in cases of endoscopy-related perforation and/or pneumoperitoneum.